Development of Educational Tourism Model Based on Local Competency at Sangkhom Islam Wittaya School Thailand - Gustia, Helfi; Haryanto, Lorenta In; Darto, Darto; Hendrawati, Tri Yuni; Mahendra, Okta; Lemsoh, Jarunee (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2024)
Sangkhom Islam Wittaya School is a privately owned Islamic school that provides standardized subjects and is overseen by the Songkhla Provincial Private Education Office. Despite being situated in a region renowned for its tourism potential, its allure remains untapped. This activity aimed to address the challenges partners overcome by developing educational approaches incorporating tourism principles. The activity commenced with a survey in 2023 and proceeded with coaching sessions from January to March 2024. The partners comprised six Sangkhom Islam Wittaya School administrators and numerous Primary and Junior High School students. This community service program employed a qualitative method integrating descriptive and explanatory approaches. Primary data collection involved conducting interviews, making observations, and organizing focus group discussions (FGDs). On the other hand, secondary data was obtained from reports, books, and other published materials. The observed tourist attractions encompassed floating markets, culinary establishments, souvenir stores, Buddhist temples and statues, hilltop museums, wayside businesses, and other similar attractions, all meticulously documented as recommended places to visit. The guided visit was divided into two days based on distance analysis. The authors suggested some places on the trip around. On the first day, students can visit Hat Yai Municipal Park, Khlong Hae Floating Market, and Kim Yong Market. On the second day, students explore Samila Beach, Songkhla Old Town, and the Folklore Museum. The findings of the partner satisfaction survey indicated that the partners expressed delight with the program implementation.